Pembelajaran Berbasis Komputer Menggunakan Ms. Office 2019 Pada Siswa Di Smk Dwitunggal 1 Tanjung Morawa - Dharmawati dharmawati; Imran Lubis; Risko Liza (Universitas Lancang Kuning, 2020)
The work world related to office administration, mastery of Microsoft Office is needed as an office administration work tool that must be mastered by vocational students. However, students of SMK Dwitunggal 1 Tanjung Morawa hasn’t been maximal in mastering Microsoft Office 2019, especially in making mail merge on Ms. Word. They are only limited to know the use of Microsoft Office 2019 in the basic stages. Community Service Activity aimed to provide training on introduction of Microsoft Office 2019 computer applications in making mail merge on Microsoft Word to students of SMK Dwitunggal 1 Tanjung Morawa majoring in Office Management. The method used in this service activities were the tutorial, the question and answer, and the practical method. This activity was done well and gained the expected results. The result of this activity was students’ improvement in the ability and skills of making mail merge for letters, certificates and labels using Microsoft Office 2019. It hoped that Students of SMK Dwitunggal 1 Office Management Department understands to create mail for letters, certificates and labels, and if they follow Competency Test for their mail merge material, they can pass and get a Competency Certificate that is given by the State.